Studi Kualitatif Terhadap Indigenous People Papua Yang Terpapar Globalisasi Budaya Melalui Relasi Sosialnya Dengan Pendatang - PRT Paramma; Lewi Kabanga (LP2M, 2021)
It has become a common understanding that the phenomenon known as globalization very quickly takes over almost all aspects of human life in different parts of the world. The majority of people have realized that they are being affected by globalization so that they are usually more readily and easily adapt to a new community called global village. However, many people are still experiencing cultural shock and lack of self-confident when meeting with people from other external environments. This latter type is usually coming from isolated areas, both physically and mentally. This study aims to explore the questions raised in the community about the effects of globalization and their relationship with the social bonds between indigenous Papuan and migrants outside of Papua. In addition, this study tries to answer the scale of acceptance of indigenous Papuans on the influence of external culture. This research is expected to provide benefits to policy makers in designing social engineering in order to avoid potential open conflicts in the future. This research method was descriptive qualitative. Data was generated from research directly on the ground through in-depth interviews (IDI) and focus group discussions (FGD). This research was conducted in the city of Jayapura. The conclusion of this study consisted of 6 measured categories, namely food / cuisine, style, social lifestyle, language, music and inter-racial marriage, which showed that the exposure to cultural globalization had a positive contribution to the social relations of indigenous Papuans with immigrants.